Quality standards for the management of non-alcoholic fatty liver disease (NAFLD): consensus recommendations from the British Association for the Study of the Liver and British Society of Gastroenterology NAFLD Special Interest Group. (August 2022) - McPherson, Stuart; Armstrong, Matthew J; Cobbold, Jeremy F; Corless, Lynsey; Anstee, Quentin M; Aspinall, Richard J; Barclay, Stephen T; Brennan, Paul N; Cacciottolo, Tessa M; Goldin, Robert D; Hallsworth, Kate; Hebditch, Vanessa; et al.
Summary: Non-alcoholic fatty liver disease (NAFLD) is common, affecting approximately 25% of the general population. The evidence base for the investigation and management of NAFLD is large and growing, but there is currently little practical guidance to support development of services and delivery of care. To address this, we produced a series of evidence-based quality standard recommendations for the management of NAFLD, with the aim of improving patient care. A multidisciplinary group of experts from the British Association for the Study of the Liver and British Society of Gastroenterology NAFLD Special Interest Group produced the recommendations, which cover: management of people with, or at risk of, NAFLD before the gastroenterology or liver clinic; assessment and investigations in secondary care; and management in secondary care. The quality of evidence for each recommendation was evaluated by the Grading of Recommendation Assessment, Development and Evaluation tool. An anonymous modified Delphi voting process was conducted individually by each member of the group to assess the level of agreement with each statement. Statements were included when agreement was 80% or greater. From the final list of statements, a smaller number of auditable key performance indicators were selected to allow services to benchmark their practice. It is hoped that services will review their practice against our recommendations and key performance indicators and institute service development where needed to improve the care of patients with NAFLD.